FAKTOR PENGHAMBAT PELAKSANAAN EVALUASI PROGRAM BIMBINGAN DAN KONSELING OLEH GURU BIMBINGAN DAN KONSELING DI SMA NEGERI KOTA PADANG - Triyono, Triyono; Sano, Afrizal; Kasih, Fitria (Bimbingan dan Konseling, 2013)
The researchers raised concerns about the study: What are the factors inhibiting the implementation of the guidance and counseling program evaluation by teachers and guidance counseling in SMA Negeri Padang City. The research objective was to describe: (1) Internal factors inhibiting the implementation of the guidance and counseling program evaluation by teachers guidance and counseling. (2) External factors inhibiting the implementation of the guidance and counseling program evaluation by teachers guidance and counseling. This research is a descriptive. The population the guidance and counseling teachers amounting 89 people. A technique used in the sampling is random sampling cluster. So the total sample of 30 people. The instrument used in this study was a questionnaire. While the percentage of data analysis techniques used. The results of this study revealed that: (1) A total of 31.1% of teacherâs guidance and counselingÂ  experiencing barriers to internal factor guidance and counseling program evaluation. (2) A total of 28.4% of teacherâs guidance and counseling experiencing barriers to external factors guidance and counseling program evaluation.